Synthesis, Structural Characterization of a Novel Ferrocene Derivative and Preliminarily Anticancer Activity - Yong, Jianping; Wu, Xiaoyuan; Liao, Jianzhen; Lu, Canzhong; Liu, Xiaolong (Medicinal Chemistry, 2016)
A novel structure of ferrocene derivative 1 was synthesized with cyanuric chloride and ferrocenemethanol as starting materials. The synthesized compound was fully characterized using 1H NMR, 13C NMR, MS and XRD. Subsequently, the in vitro anticancer effect against A549, HCT116 and MCF-7 cell lines was preliminarily evaluated by the MTT method. The result showed that this compound exhibits good cytotoxic effect on A549, HCT116 and MCF-7 cell lines.
Keywords: XRD